Antimicrobial Photodynamic Therapy in the Control of COVID-19 - Almeida, Adelaide (Antibiotics (Basel), 2020)
Antimicrobial photodynamic therapy (aPDT), using well known, safe and cost-effective photosensitizers, such as phenothiazines, e.g., methylene blue (MB), or porphyrins, e.g., protoporphyrin-IX (PP-IX), might help to mitigate the COVID-19 either to prevent infections or to develop photoactive fabrics (e.g., masks, suits, gloves) to disinfect surfaces, air and wastewater, under artificial light and/or natural sunlight.